Individualized Treatment Algorithm Using Hyaluronic Acid Fillers for Lifting, Contouring and Volumizing the Midface - Di Gregorio, Carlo; Gauglitz, Gerd; Partridge, Jackie (Clinical, cosmetic and investigational dermatology, 2022)
Patients seeking treatment for the midface are individuals with different objectives and characteristics of skin and soft tissue. In this study, patients were treated in the midface with one of three products with different properties; HA , HA , or HA , using a treatment algorithm based on primary need for treatment (volumizing, lifting or contouring) and tissue coverage (thin or thick tissue). The aim was to optimize the treatment outcome and to provide an individualized treatment approach that distinguishes different types of patients seeking midfacial treatment. Subjects were treated in the midface at baseline to achieve optimal aesthetic results (≤2 mL per side of the face), and touch-up was allowed after 4 weeks (≤1 mL per side of the face). Study visits were scheduled at Weeks 8, 16 and 24. Assessments included aesthetic improvement of the midface, evaluation of midface fullness, and subject satisfaction. Safety evaluations included local tolerability symptoms collected at 4 weeks after treatment and adverse events. A total of 90 subjects were included in the study, mean age was 45 years (range 29-55) and 82% of subjects were female. Mean total injected volume for the products was 4.4 mL (HA and HA ) and 4.2 mL (HA ). At least 92% of subjects were assessed as aesthetically improved throughout the study. Assessment of midface fullness showed ≥90% of subjects being responders until Week 24. In addition, subject satisfaction was high throughout the study. Tenderness, bruising and swelling were the most reported local tolerability symptom for all study products, and no adverse events related to study product/treatment were reported. Midface treatment with either HA , HA , or HA using a treatment algorithm to guide the choice of product to individual subject needs was effective and safe for up to 24 weeks after treatment.